1997
DOI: 10.1007/s004390050524
|View full text |Cite
|
Sign up to set email alerts
|

Detection of chromosomal aneuploidy in endometriosis by multi-color fluorescence in situ hybridization (FISH)

Abstract: Endometriosis affects 10-15% of women of reproductive age and is a common cause of infertility and pelvic pain. Although endometriosis is characterized by abnormal growth or turn-over of cells, the genetic changes involved remain unclear. We employed a multi-color fluorescence in situ hybridization (FISH) strategy to determine the incidence of somatic chromosomal numeric alterations in severe/late stage endometriosis. Using alpha-satellite sequence-specific DNA probes for chromosomes 7, 8, 11, 12, 16, 17, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 18 publications
1
19
1
2
Order By: Relevance
“…However, recent molecular allelotyping work has detected somatic genetic changes, expressed as loss of heterozygosity (LOH) distributed along several chromosomes in 11 of 40 (28%) endometriotic samples (Jiang et al 1998). Moreover, clonal expansion of abnormal cells with monosomies 16 and 17 and trisomy of chromosome 11 was reported in ovarian endometriomas using the FISH strategy (Shin et al 1997).…”
Section: Introductionmentioning
confidence: 98%
“…However, recent molecular allelotyping work has detected somatic genetic changes, expressed as loss of heterozygosity (LOH) distributed along several chromosomes in 11 of 40 (28%) endometriotic samples (Jiang et al 1998). Moreover, clonal expansion of abnormal cells with monosomies 16 and 17 and trisomy of chromosome 11 was reported in ovarian endometriomas using the FISH strategy (Shin et al 1997).…”
Section: Introductionmentioning
confidence: 98%
“…The most widely accepted candidate for the origin of ovarian cancer is the so-called ovarian surface epithelium (OSE), a single layer of fl attened cells covering the ovarian surface. Pathological fi ndings have shown that OSE can be endowed tion, or microsatellite analysis have revealed genomic abnormalities, such as loss of heterozygosity (LOH) of chromosomes 1p, 9p, 11q, 17p, and 22q, and amplifi cation of 17q, [16][17][18][19] again indicating the clonal evolution of this disease. Sato et al 20 reported somatic mutation of PTEN in solitary endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…Other evidence of a genetic basis for endometriosis comes from nonhuman primates (26). Molecular and cytologic research has suggested a possible path for genetic control of endometriosis (27,28). Several candidate genes have been identified for investigation, including genes involved in galactose metabolism and dioxin detoxification (22).…”
mentioning
confidence: 99%